Detection of circulating neoplastic cells by reverse-transcriptase polymerase chain reaction in malignant melanoma: association with clinical stage and prognosis - Mellado, B; Colomer, D; Castel, T; Muñoz, M; Carballo, E; Galán, M; Mascaró, J M; Vives-Corrons, J L; Grau, J J; Estapé, J (Journal of clinical oncology, 1996)
Circulating melanoma cells can be detected in peripheral blood by means of tyrosinase mRNA amplification by reverse-transcriptase polymerase chain reaction (RT-PCR). We conducted a prospective study to evaluate the clinical significance of the presence of circulating neoplastic cells in the blood of patients with malignant melanoma (MM). A sensitive RT-PCR assay was used to detect tyrosinase mRNA in the peripheral blood of patients with stages I to IV melanoma. Healthy subjects or patients with other malignancies were used as negative controls. Ninety-one assessable patients were included in the study. There was a statistically significant association between RT-PCR positivity and clinical stage. Circulating melanoma cells were detected in 36% of patients with localized disease (stages I and II), in 45% of patients with regional nodal involvement (stage III), and in 94% of patients with metastatic disease (stage IV) (P < .001). In stage II-III patients who were RT-PCR-positive for mRNA tyrosinase in blood, the recurrence rate and disease-free survival were significantly worse than patients who were RT-PCR-negative. In multivariate analysis, RT-PCR was an independent prognostic factor for recurrence in patients with nonmetastatic disease (P = .002). The detection of circulating melanoma cells in peripheral blood by RT-PCR correlated with the clinical stage of patients with melanoma and was an independent prognostic factor for recurrence. Further studies are warranted to better assess the significance of this test in the evaluation of prognosis, early detection of relapse, and in monitoring the effectiveness of systemic therapy.